Constraints in Role Performance of Gram Panchayat in Agriculture - Anuradha Ranjan Kumari; Laxmikant (Journal of Agricultural Extension Management, 2015)
A study was conducted in Pusa block of Samastipur district in Bihar to find out and prioritize the constraints in role performance of Gram Panchayats in agriculture. The total number of respondents (Gram Panchayat members including Mukhiya) selected for the study was 75. An open ended schedule was devised to identify and Garrett ranking technique (1981) was used to prioritize the constraints. The results of the study show that lack of maintenance of resource inventory, provision of funds mostly at the end of the financial year, non availability of committed cash and kind in matching amount at the appropriate time, substandard quality of production inputs, inadequate availability of technical and non technical manpower, inadequate and lack of timely availability of production inputs, lack of technical know-how, lack of viable and need oriented projects, insufficient computer facilities etc. were among the most important perceived constraints